ILLOCUTIONARY ACT IN DANGEROUS MIND MOVIE DIRECTED BY JOHN N. SMITH - Suprayitno, Hadi; Wulandari, Rifa Suci; Ro'is, Syamsuddin (STKIP PGRI Ponorogo Press, 2022)
Illocutionary act was part of Speech Act. Speech acts is a branch of pragmatics that analyses the performance of an utterance in context. In this case, context gives influence in meaning of utterances. In this study, the researcher analyzed illocutionary act and context of situation in the main character’s utterances of Dangerous Mind movie directed by John N. Smith. The researcher used descriptive qualitative research to analyze the illocutionary act and context of situation within the movie. The researcher took the data from the main character’s utterances. In collecting data, the researcher used documentation technique and then analysed the data by employing qualitative analysis suggested by Miles and Huberman. Based on the analysis, the writer found five categories of illocutionary act in Dangerous Mind movie. They were 29 utterances including directives, 26 utterances including expressive, 17 utterances including commissives, 5 utterances on declarations and 24 utterances on representatives. Directives are the most dominant act used by main characters with 29 utterances. The context of a situation is background that affected the hearer’s interpretation of utterances produced by the speaker.